Foliar nutrient allocation patterns in Banksia attenuata and Banksia sessilis differing in growth rate and adaptation to low-phosphorus habitats - Han, Zhongming; Shi, Jianmin; Pang, Jiayin; Yan, Li; Finnegan, Patrick M; Lambers, Hans (Annals of botany, 2021)
Phosphorus (P) and nitrogen (N) are essential nutrients that frequently limit primary productivity in terrestrial ecosystems. Efficient use of these nutrients is important for plants growing in nutrient-poor environments. Plants generally reduce foliar P concentration in response to low soil P availability. We aimed to assess ecophysiological mechanisms and adaptive strategies for efficient use of P in Banksia attenuata (Proteaceae), naturally occurring on deep sand, and B. sessilis, occurring on shallow sand over laterite or limestone, by comparing the allocation of P among foliar P fractions. We carried out pot experiments with slow-growing B. attenuata, which resprouts after fire, and faster growing opportunistic B. sessilis, which is killed by fire, on substrates with different P availability using a randomized complete block design. We measured leaf P and N concentrations, photosynthesis, leaf mass per area, relative growth rate and P allocated to major biochemical fractions in B. attenuata and B. sessilis. The two species had similarly low foliar total P concentrations, but distinct patterns of P allocation to P-containing fractions. The foliar total N concentration of B. sessilis was greater than that of B. attenuata on all substrates. The foliar total P and N concentrations in both species decreased with decreasing P availability. The relative growth rate of both species was positively correlated with concentrations of both foliar nucleic acid P and total N, but there was no correlation with other P fractions. Faster growing B. sessilis allocated more P to nucleic acids than B. attenuata did, but other fractions were similar. The nutrient allocation patterns in faster growing opportunistic B. sessilis and slower growing B. attenuata revealed different strategies in response to soil P availability which matched their contrasting growth strategy.